2010
DOI: 10.1111/j.1349-7006.2010.01786.x
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase activation without shortening of telomeric 3′‐overhang is a poor prognostic factor in human colorectal cancer

Abstract: Our previous report demonstrated a good correlation between high telomerase activity of cancer tissues and a poor prognosis of patients with colorectal cancers, except for several cases. To elucidate the additional factors that contribute to patient prognosis, the correlation among the expression levels of telomere binding proteins (TBP), the lengths of telomeres, the lengths of telomere 3¢-overhang (3¢-OH) and telomerase activity in 106 paired colorectal cancer and corresponding noncancerous mucosa (NCM) spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…Previous studies have suggested that the maintenance of telomere length through the reactivation of telomerase is a prerequisite for tumors to preserve their ability to proliferate and grow [8][9][10][11]. So far, there were several studies exploring the prognostic role of telomere length in colorectal cancer, but no consistent findings were reported [12][13][14][15][16]. Therefore, it is necessary to assess all data and elucidate those controversial or inconclusive results.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…Previous studies have suggested that the maintenance of telomere length through the reactivation of telomerase is a prerequisite for tumors to preserve their ability to proliferate and grow [8][9][10][11]. So far, there were several studies exploring the prognostic role of telomere length in colorectal cancer, but no consistent findings were reported [12][13][14][15][16]. Therefore, it is necessary to assess all data and elucidate those controversial or inconclusive results.…”
Section: Introductionmentioning
confidence: 92%
“…The number of participants with colorectal cancer ranged from 57 to 571 (Table 1). The study by Kojima et al reported that telomere length was not associated with the survival of colorectal cancer, but didn't report the exact HR with 95%CI [13]. The outcome of quality assessment was shown in the Table 1.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have also found that telomerase can induce cell expression of epidermal growth factor (EGFR) (39) or transforming growth factor-β (TGF-β) (40) to stimulate cell proliferation. In fact, prognostic values of TA for overall survival in CRC patients are significantly correlated, those who had telomerase activated without 3'OH shortened telomeres had a poor prognosis (41). Patients with telomerase negative tumors had better overall survival than patients with telomerase positive tumors (19).…”
Section: Discussionmentioning
confidence: 99%